Auditory and visual impact of split systems on the façade of historical buildings. (July 2021) - Masullo, Massimiliano; Pellegrino, Rossana; Scorpio, Michelangelo; Maffei, Luigi
Abstract: In the last decades, the demand for air conditioning and cooling systems for buildings continues to increase, despite the awareness campaigns and the Green Policies adopted by European Countries. The adoption of such policies is dictated by climate change, and by the will to reduce GHG emissions and increase the use of energy from renewable sources. Among all the different air conditioning systems, the split systems represent most Room Air Conditioners (RAC) units installed in Europe. Their integration with the buildings of historical centres is not successful due to the sound emissions of external units and their visual impact on buildings' facades. The acoustic and the visual impact are evaluated separately, by comparing the results of outdoor noise prediction models with noise limits levels at receivers or using local regulations. A virtual reality environment has been prepared to carry out a laboratory experiment to understand better how Air Conditioning (AC) split units affect the residents' overall perceptions. This paper investigates the combined (auditory and visual) impacts of installing external units of split systems on historical buildings' facades. By combining different Visual Aspects and Noise Levels, the noise annoyance and other perceptual attributes of the environment have been studied. Main conclusions suggest that visual elements more integrated on the façade of the historical building can help reduce the auditory and the visual impact of these elements. Moreover, well-integrated and pleasant elements led to a lower auditory perception of the loudness and noise annoyance than less integrated elements.